Scaling up sweetpotato through agriculture and nutrition in Kenya - Muoki, Penina Ngusye; Agili, S. (International Potato Center, 2015)
SUSTAIN is a 5-year partnership (2013-2018), coordinated by CIP and financed by the UK Department for International Development, to scale up the nutrition benefits of biofortified orange-fleshed sweetpotato (OFSP). The goal is to reach 1.2 million households with under-5 year old children in Kenya, Malawi, Mozambique, and Rwanda. In Kenya, SUSTAIN has set out to reach 35,000 households with children under 5 years of age with OFSP vines and nutrition education by 2018. This is a summary of the progress made towards this goal from June 2014 to July 2015.